PELATIHAN PENGGUNAAN ZOTERO UNTUK MAHASISWA SEBAGAI BEKAL DALAM PENULISAN KARYA ILMIAH - Citrakara Upendra Sneha Bandhana Kusuma Himawan; Alfian Hudan Laksan; Rizki Fillya (Jurnal Pemantik, 2023)
Indicators or references for scientific papers can be said to be good if they are avoided duplication or plagiarism elements. Plagiarism often occurs among students, especially in writing/compiling scientific works. Many students write citations in their scientific paper but do not include references in the reference list and vice versa. This phenomenon occurs because there are still many students who are not familiar with reference tools such as Zotero, End-note, etc. Based on this, this community service is carried out with the objectives: 1. providing an introduction to the importance of using reference tools to students in compiling scientific papers to reduce the percentage of plagiarism, and 2. showing how to get references to students. This community service is carried out through introduction (socialization) and online training with students of the Department of Mechanical Engineering, Faculty of Engineering, Pawyatan Daha University. This community service is carried out using lectures, discussions, and assignments to students to do installations, create accounts, and finally make citations and references. Community service activities have results showing that students can install and use Zotero in making citations and reference lists.